Prevalence and Antibiotic Resistance of Carbapenemase-Producing Gram-Negative Bacteria in Saint Petersburg and Some Other Regions of the Russian Federation - I. V. Lazareva; V. A. Ageevets; T. A. Ershova; L. P. Zueva; A. E. Goncharov; M. G. Darina; Yu. S. Svetlichnaya; A. N. Uskov; S. V. Sidorenko (Антибиотики и Химиотерапия)
Carbapenemase-producing gramnegative bacteria, which hydrolyze most ofв-lactams, including carbapenems, is of global health care system threat. The number of the known carbapenemases is constantly increasing, however only four types are widely distributed: NDM-type, KPC-type, OXA-48-type and VIM-type. The frequency of carbapenemase-producing Klebsiella pneumoniae in hospitals of Saint Petersburg reached 9.2% (5.9% for NDM-type, 1.4% for ОХА-48-type, 1.9% for NDM-type + ОХА-48-type). Carbapenemase producers were also detected in hospitals of Moscow, Yekaterinburg, Vologda, Murmansk, Kurgan, Krasnoyarsk, Izhevsk, Krasnodar and Perm. In total 281 carbapenemase producers were recorded within 2011-2016, which were isolated from infected or colonized patients (K.pneumoniae - 247 isolates, Acinetobacter spp - 29 isolates, Enterobacter cloacae - 2 isolates, Serratia marcescens - 1 isolate, Escherichia coli - 1 isolate and Proteus mirabilis - 1 isolate). The carbapenemase-producing K.pneumoniae isolates were distinguished by considerable genetic diversity, the NDM-type carbapenemase-producers belonged to eight, КРС-type - to three and ОХА-48-type - to four different sequence-types (STs) respectively. The representatives of the globally dominant genetic line, Clonal Group 258 (CG258), and also a number of the less common lines (ST147, ST273, ST307 and ST377) were detected. The K.pneumoniae strains were distinguished by a high frequency of cross-resistance and the associated resistance to antibiotics of different groups. The frequency of resistance to cephalosporins and fluoroquinolones reached 100%. Among the NDM-type carbapenemase producers the frequency of resistance to aminoglycosides exceeded 90%, among the КРС-type carbapenemase producers the frequency of resistance corresponded to 66% for amikacin and 93% for gentamicin, among the ОХА-48 type carbapenemase producers the frequency of resistance was even lower (50% and 73% respectively). Approximately 80% of the NDM-type, 90% of the КРС-type and only 60% of the ОХА-48-type carbapenemase producers showed a high level of resistance to imipenem and meropenem. The frequency of resistance to tigecycline varied within 6.7% to 14.8% and the frequency of resistance to polymyxin was within 4.2% to 20%. The ОХА-40- and ОХА-23-types carbapenemase-producing Acinetobacter spp. remained susceptible only to polymyxin. It is obvious that the possibility of antibacterial therapy of infections caused by carbapenemases producers is limited.